(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: To describe the current situation of post-operation painkillers use at the general surgery department of Cai Nuoc General Hospital. Objects and methods: Cross-sectional descriptive study on 172 patients undergoing surgery at General Surgery Department, Cai Nuoc General Hospital. Results: Mainly using paracetamol for pain relief, accounting for 98.98%. For epidural painkillers (levobupivacaine and fentanyl), the rate of use decreased significantly when comparing group 1 with group 2. This difference was statistically significant (p <0.05). The average number of drugs studied by patients in both groups for post-operative painkillers was 3.3 ± 1.2 types. Group 1 had patients using the main combination of drugs for post-operative painkillers was epidural (Levobupivacaine, fentanyl) + Ketorolac + Paracetamol with the rate of 48.81%. Group 2 had patients using a combination of drugs mainly to relieve pain after surgery was Morphin + Ketorolac + Paracetamol with the rate of 40.91%. Conclusion: Paracetamol was the primary painkillers. The average number of drugs for post-operative painkillers was 3.3 ± 1.2 types. Group 1 patients using the combination drug was epidural mainly (Levobupivacaine, fentanyl) + Ketorolac + Paracetamol. Group 2 patients using the combination of drugs was Morphin + Ketorolac + Paracetamol, mainly.